STRUCTURAL DESIGN STUDY OF ABUTMENTS USING BORED PILE FOUNDATIONS BRIDGE BESUK BONDOWOSO - M. Rifki Alfaries; Ilanka Cahya Dewi; Arief Alihudien; Hilfi Harisan Ahmad; Jimi Amijaya (Jurnal Pensil : Pendidikan Teknik Sipil, 2026)
This study aims to analyze and plan the abutment structure with bored pile foundations on the Besuk Bridge in Klabang District, Bondowoso Regency, East Java. The analysis was conducted to ensure the bearing capacity of the bored piles against axial and lateral loads in accordance with SNI 1725:2016 and SNI 2833:2016. The data used includes soil data from field investigations, shop drawings, and structural design parameters. The calculation process includes determining load combinations, analyzing axial bearing capacity (end resistance and skin friction), and the lateral capacity of piles against horizontal forces due to wind and earthquakes. The analysis results show that the total axial bearing capacity of the foundation is 10,465.26 kN, with a maximum load occurring on the pile of 1,262.56 kN, which is still below the allowable capacity. Meanwhile, the results of the lateral load control show that all load combinations produce lateral forces (Tx and Ty) that are smaller than the allowable capacity. Based on these results, the bored pile foundation with a diameter of 0.8 m and a depth of 10 m is deemed safe to withstand both axial and lateral loads. Thus, the design of the abutment structure and bored pile foundation for the Besuk Bridge meets the stability and strength criteria in accordance with applicable design standards.